Enhancing multiplex genome editing by natural transformation (MuGENT) via inactivation of ssDNA exonucleases. Issue 12 (31st May 2017) - Dalia, Triana N.; Yoon, Soo Hun; Galli, Elisa; Barre, Francois-Xavier; Waters, Christopher M.; Dalia, Ankur B.
Abstract: Recently, we described a method for multiplex genome editing by natural transformation (MuGENT). Mutant constructs for MuGENT require large arms of homology (>2000 bp) surrounding each genome edit, which necessitates laborious in vitro DNA splicing. In Vibrio cholerae, we uncover that this requirement is due to cytoplasmic ssDNA exonucleases, which inhibit natural transformation. In ssDNA exonuclease mutants, one arm of homology can be reduced to as little as 40 bp while still promoting integration of genome edits at rates of ∼50% without selection in cis . Consequently, editing constructs are generated in a single polymerase chain reaction where one homology arm is oligonucleotide encoded. To further enhance editing efficiencies, we also developed a strain for transient inactivation of the mismatch repair system. As a proof-of-concept, we used these advances to rapidly mutate 10 high-affinity binding sites for the nucleoid occlusion protein SlmA and generated a duodecuple mutant of 12 diguanylate cyclases in V. cholerae . Whole genome sequencing revealed little to no off-target mutations in these strains. Finally, we show that ssDNA exonucleases inhibit natural transformation in Acinetobacter baylyi . Thus, rational removal of ssDNA exonucleases may be broadly applicable for enhancing the efficacy and ease of MuGENT in diverse naturally transformable species.